Revealing the Real Charge Carrier in Aqueous Zinc Batteries Based on Polythiophene/Manganese Dioxide Cathode. Issue 2 (28th November 2022) - Huang, Xinjun; Liu, Xiaohui; Li, Hui; Zhao, Qin; Ma, Tianyi
Abstract : The rechargeable aqueous zinc–manganese dioxide (Zn–MnO2 ) batteries are promising candidates for grid‐scale energy storage because of their high energy density and safety, low cost, and environmental friendliness. Unfortunately, capacity fading and ambiguous energy storage mechanisms are obstacles to the commercial application of Zn–MnO2 batteries. Herein, the polythiophene (PTh)‐MnO2 (PTM) nanocomposites are synthesized through a simple and low‐energy consumption interfacial polymerization method. Benefiting from the flexibility and high conductivity of PTh, the PTM electrodes exhibit high reversible specific capacity, acceptable rate performance, and impressive cycle life. Furthermore, ex situ characterizations of the PTM electrodes reveal that the real charge carriers are protons (H + ) and hydrated alkaline zinc sulfate (ZSH) is the main product during the discharge state of Zn‐PTM batteries. Consequently, the reversible H + insertion/extraction accompanying the formation/dissolution mechanism of the Zn‐PTM battery is proposed. In addition, the Zn‐PTM pouch battery as a power source can drive 3C commodities even under striking and piercing conditions. This study not only offers a promising strategy to scale synthesize cathode materials but also promotes insight into energy storage mechanisms and practical applications for aqueous zinc batteries. Abstract : Protons are the real charge carriers in aqueous Zn‐polythiophene manganese dioxide (PTM) batteries. With the formation of dense hydrated alkaline zinc sulfate (ZSH) on the surface of the PTM electrode, the protons insert into the PTM electrode through the intermolecular hydrogen bonds of ZSH, maintaining the continuous discharge process.